Properties of the Band Gaps in 1D Ternary Lossy Photonic Crystal Containing Double-Negative Materials. (13th February 2014) - Aghajamali, Alireza; Akbarimoosavi, Maryam; Barati, Mahmood
Abstract : Theoretically, the characteristics matrix method is employed to investigate and compare the properties of the band gaps of the one-dimensional ternary and binary lossy photonic crystals which are composed of double-negative and double-positive materials. This study shows that by varying the angle of incidence, the band gaps for TM and TE waves behave differently in both ternary and binary lossy structures. The results demonstrate that, by increasing the angle of incidence for the TE wave, the width and the depth of zero-n ¯, zero-μ, and Bragg gap increase in both ternary and binary structures. On the other hand, the enhancement of the angle of incidence for the TM wave contributes to reduction of the width and the depth of the zero-n ¯ and Bragg gaps, and they finally disappear for incidence angles greater than 50° and 60° for the binary structure and 40° and 45° for the ternary structures, respectively. In addition, the details of the edges of the band gaps variations as a function of incidence angle for both structures are studied.